We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
185
3
avatar

Compute 1*1/2+2*1/3+3*1/8+...+n*1/2^n+...

 

if you guys could solve this then that would be great!

 Sep 13, 2018
 #1
avatar+22196 
+8

I assume: Compute 1*1/2+2*1/4+3*1/8+...+n*1/2^n+...

 

Compute:

\(\displaystyle s = 1\cdot \dfrac12+2\cdot\dfrac14+ 3\cdot \dfrac18+ 4\cdot \dfrac{1}{16}+\ldots + n\cdot \dfrac{1}{2^n}+\ldots \infty\)

 

\(\begin{array}{|lrll|} \hline &s =& \displaystyle 1\cdot \dfrac12+2\cdot\dfrac14+ 3\cdot \dfrac18+ 4\cdot \dfrac{1}{16}+\ldots + n\cdot \dfrac{1}{2^n}+\ldots \infty \\\\ &s =& \displaystyle 1\cdot \left(\dfrac12\right)^1+2\cdot\left(\dfrac12\right)^2+ 3\cdot \left(\dfrac12\right)^3+ 4\cdot \left(\dfrac{1}{2}\right)^4+\ldots + n\cdot \left(\dfrac{1}{2} \right)^n+\ldots \infty \\\\ && \displaystyle\qquad \text{We substitute:} \quad \boxed{x=\dfrac12} \\\\ &s =& \displaystyle 1x^1+2x^2+ 3x^3+ 4x^4+\ldots + nx^n+\ldots \infty \quad | \quad : x \\\\ &\dfrac{s}{x} =& \displaystyle 1x^0+2x^1+ 3x^2+ 4x^3+\ldots + nx^{n-1}+\ldots \infty \\\\ &\dfrac{s}{x} =& \displaystyle \sum \limits_{n=1}^{\infty} nx^{n-1} \quad | \quad \cdot \ dx \\\\ &\dfrac{s}{x}\ dx =& \displaystyle \sum \limits_{n=1}^{\infty} \left( nx^{n-1}\ dx \right) \quad | \quad \text{integrate both sides} \\\\ &\int \dfrac{s}{x}\ dx =& \displaystyle \int \left(\sum \limits_{n=1}^{\infty} \left( nx^{n-1}\ dx \right) \right) \\\\ &\int \dfrac{s}{x}\ dx =& \displaystyle \sum \limits_{n=1}^{\infty} x^{n} \quad | \quad \text{This is the sum of a infinite geometric series},\ a_1=x,\ r=x \\\\ && \displaystyle\qquad \text{The sum of this infinite geometric series is:} \quad \boxed{= \dfrac{x}{1-x},\ \quad |x| \lt 1 } \\\\ &\int \dfrac{s}{x}\ dx =& \displaystyle \dfrac{x}{1-x} \quad | \quad \text{derivate both sides} \\\\ & \dfrac{s}{x} =& \displaystyle 1\cdot(1-x)^{-1}+x\cdot(-1)\cdot(1-x)^{-2}\cdot(-1) \\\\ & \dfrac{s}{x} =& \displaystyle \dfrac{1}{1-x} + \dfrac{x}{(1-x)^2} \\\\ & \dfrac{s}{x} =& \displaystyle \dfrac{1-x+x}{(1-x)^2} \\\\ & \dfrac{s}{x} =& \displaystyle \dfrac{1}{(1-x)^2} \\\\ & \mathbf{s=}& \mathbf{\displaystyle \dfrac{x}{(1-x)^2}} \quad | \quad x=\dfrac12 \\\\ & s= & \displaystyle \dfrac{\dfrac12}{\left(1-\dfrac12 \right)^2} \\\\ & s= & \displaystyle \dfrac{\dfrac12}{\left(\dfrac12 \right)^2} \\\\ & s= &\displaystyle \dfrac{1}{ \dfrac12 }\\\\ & \mathbf{s=}& \mathbf{\displaystyle 2} \\ \hline \end{array}\)

 

\(\displaystyle 1\cdot \dfrac12+2\cdot\dfrac14+ 3\cdot \dfrac18+ 4\cdot \dfrac{1}{16}+\ldots + n\cdot \dfrac{1}{2^n}+\ldots \infty = 2\)

 

laugh

 Sep 13, 2018
edited by heureka  Sep 13, 2018
 #3
avatar
+2

Thanks!

Guest Sep 13, 2018
 #2
avatar+27852 
+3

Heureka beat me to it! However, Here's my attempt anyway (like heureka, I've assumed the second term was written incorrectly in the original question):

 

.

 Sep 13, 2018

7 Online Users

avatar